Comparison of intravenous AH 5158 (ibidomide) and propranolol in asthma. Issue 5962 (12th April 1975) - Skinner, C; Gaddie, J; Palmer, K N
Abstract : The cardiac and bronchial effects of AH 5158 and propranolol were compared in a double-blind, placebocontrolled intravenous study on 10 asthmatics. AH 5158, like propranolol, is a non-cardioselective beta-adrenoceptor-blocking drug, but unlike propranolol it also has an alpha-adrenoceptor-blocking action. Both drugs produced equivalent cardiac(beta1) blockade, but propranolol produced bronchoconstriction, whereas AH 5158 did not. Hence the alpha-blocking action of AH 5158 seems to prevent the bronchoconstrictor effects of propranolol in these patients.